1981
DOI: 10.1128/jcm.13.4.655-660.1981
|View full text |Cite
|
Sign up to set email alerts
|

Detection of yeast septicemia by biphasic and radiometric methods

Abstract: microbiology laboratory used a commercial biphasic brain heart infusion vented culture method for fungal blood cultures and a commercial radiometric (BACTEC 460, Johnson Laboratories, Cockeysville, Md.) method for bacterial blood cultures. A total of 668 biphasic fungal blood cultures were processed, of which 30 grew yeasts from 19 patients. There were 38,324 BACTEC blood cultures processed for bacteria, of which 184 grew yeasts from 85 patients. The overall detection time for all yeasts averaged 8.3 days for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…As in the present study, several investigators have observed a faster detection speed in BAC-TEC@ systems as compared to conventional systems, including biphasic systems (2,18,21,23,26). We found clinically significant microorganisms on average 1 day faster in the B A C T E P system, which was in agreement with Weinstein et al (26).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As in the present study, several investigators have observed a faster detection speed in BAC-TEC@ systems as compared to conventional systems, including biphasic systems (2,18,21,23,26). We found clinically significant microorganisms on average 1 day faster in the B A C T E P system, which was in agreement with Weinstein et al (26).…”
Section: Discussionsupporting
confidence: 72%
“…During the last decade, several more or less automated C0,-detecting systems have been introduced. A number of these systems have proved to be superior to many systems that rely on visual examination (2,18,(21)(22)(23)26), including biphasic systems (21,26). The aim of the present study was to compare the Roche BCB@ system and the newly developed automated BACTEC NR-860@ system as regards detection speed and yield.…”
mentioning
confidence: 99%
“…The detection of Candida spp. in blood cultures by the radiometric system (BACTEC R) has been shown to be superior to the conventional methods with regard to productivity and shorter times of detection of positive bottles (13,21,25). With the introduction of the nonradiometric system (BACTEC NR) into many laboratories (9,15) and the increasing importance of candidemia in recent years, an assessment of this method has become necessary.…”
mentioning
confidence: 99%
“…The introduction of the radiometric detection procedure (BACTEC R) has permitted the establishment of a mechanized routine which has demonstrated greater sensitivity in the detection of candidemia than that displayed by conventional systems (13,21,25). The radiometric system, nevertheless, has the drawbacks inherent in the handling of radioactive materials.…”
mentioning
confidence: 99%
“…When fungemia caused by C. lipolytica developed in one of our patients, we found that there was no single study which examined the clinical manifestations, microbiological features, and in vivo characteristics of this fungus. C. lipolytica was not included in several large case series as a cause of fungemia (3,7,8,13). Only one well-described case of fungemia (18) and three cases of traumatic ocular infection (11) caused by C. lipolytica have been reported previously.…”
mentioning
confidence: 99%